Role of phytobiotics in relieving the impacts of Aeromonas hydrophila infection on aquatic animals: A mini-review - Abdul Kari, Zulhisyam; Wee, Wendy; Mohamad Sukri, Suniza Anis; Che Harun, Hasnita; Hanif Reduan, Mohd Farhan; Irwan Khoo, Martina; Van Doan, Hien; Wen Goh, Khang; Seong Wei, Lee (Frontiers in Veterinary Science, 2022)
Aeromonas hydrophila is a ubiquitous bacterium with various hosts that causes mass mortality in aquaculture species and significant economic losses. The current treatment is ineffective in controlling this bacterium infection in aquaculture species. Therefore, an evaluation of potential phytobiotics is needed to find an alternative antimicrobial agent to reduce the over-reliance on antibiotics in aquaculture and safeguard public and environmental health. Furthermore, the rise in antibiotic resistance cases among pathogenic bacteria indicates an urgent need for new solutions in managing aquaculture species' health. This review will focus on the impacts of Motile Aeromonad Septicemia (MAS) due to A. hydrophila in aquaculture, the potential of phytobiotics in enhancing the tolerance of aquaculture species against MAS and the combination of phytobiotics with other antimicrobial and therapeutic agents against MAS.